The effectiveness of public expenditure on higher education and the employment in Mexico - Acosta, Rubén Macías (Linguistics and Culture Review, 2021)
Higher education is the most important element to achieve the redistribution of wealth in a country, for that reason its public spending is a subject to study, also the studied professions, the demanded professions by the market and the salaries received by them, because citizens must be able to attend the principal needs of the nation, thereby increasing their income and achieve a decent life. The objective of the document is to analyze the educational proposal considered in the National Development Plan (PND) 2019-2024 in Mexico, specifically in the objective: “2. Guarantee employment, education, health and welfare” analyzing the proposal “5. Young people writing the future, this is a national program aimed to young people who are enrolled in a center of higher education”. In the methodology, it is made a descriptive analysis of the expenditure on education, that information is published by the Chamber of Deputies in México also analyze the information of the Occupation by Economic Sectors generated by National Institute of Statistic and Geography (INEGI).